Loving the Stranger: Mixed Couples and Mixed Emotions - King-O’Riain, Rebecca (Simmel Studies)

(untitled) (Edizioni ETS, 2021)
This paper brings together two of the key theoretical concepts attributed to Georg Simmel – the notion of the ‘stranger’ (the person who is not indigenous to a social context and perpetually seen as possibly not belonging) and ‘love’ as socially constructed which has the potential to turn an individual love into a notion of ‘super individual couplehood’ unifying two individuals and transforming them in the process. Based on in-depth qualitative interviews with 35 people in ‘mixed’ couples, this paper examines how loving the stranger is constructed, maintained and challenged across cultures, languages, races, and nationalities.